Acculturation as translation: mimicry, satire and resistance in Chewa dance - Nthala, Grant (Acta Academica: Critical views on society, culture and politics, 2012)
The gulewamkulu mask dance is the major Chewa dance performed in all Chewa communities of Malawi, Zambia, Mozambique, Tanzania and Zimbabwe. With this particular dance – and indeed with many others – historical connotations, cultural reverberations, and systemic institutionalisation come into play. The hierarchical organisation of the Chewa dance systems and the orderly and enigmatic tendencies of the dance displays are reminiscent of historical phenomena linked to the Chewa diaspora. In essence, mimicry, satire and other forms of enactment (often dramatic) in Chewa dance subtly or candidly unearth acculturative elements within the Chewa ethnicity. This article seeks to illustrate that the Chewa dances gulewamkulu and mganda constitute theatre and that their performance demonstrates a manifestation of traditional Chewa cultural features that have been altered or modified by borrowing from or adapting to other Bantu-related and European cultures.